BLEMAB European project: muon imaging technique applied to blast furnaces. (1st April 2022) - ,; Bonechi, L.; Ambrosino, F.; Andreetto, P.; Bonomi, G.; Borselli, D.; Bottai, S.; Buhles, T.; Calliari, I.; Checchia, P.; Chiarotti, U.; Cialdai, C.; et al.
Abstract: The BLEMAB European project (BLast furnace stack density Estimation through on-line Muon ABsorption measurements), evolution of the previous Mu-Blast European project, is designed to investigate in detail the capability of muon radiography techniques applied to the imaging of a blast furnace's inner zone. In particular, the geometry and size of the so called "cohesive zone", i.e. the spatial zone where the slowly downward moving material begins to soften and melt, that plays an important role in the performance of the blast furnace itself. Thanks to the high penetration power of the natural cosmic ray muon radiation, muon transmission radiography represents an appropriate non-invasive methodology for imaging large high-density structures such as blast furnaces, whose linear size can be up to a few tens of meters. A state-of-the-art muon tracking system, whose design profits from the long experience of our collaboration in this field, is currently under development and will be installed in 2022 at a blast furnace on the ArcelorMittal site in Bremen (Germany) for many months. Collected data will be exploited to monitor temporal variations of the average density distribution inside the furnace. Muon radiography results will also be compared with measurements obtained through an enhanced multipoint probe and standard blast furnace models.